Synthesis and Characterisation of Calcined Zeolite X and Silica-Supported Zeolite Y - M, Abakpa A.; L, Leke; M, Twan S.; T, Japhet; J, Ewenifa O.; P, Omale, O. (African Journal of Sciences and Traditional Medicine, 2024)
Zeolite X was synthesised from rice husk silica and aluminium metal as raw materials while Zeolite Y supported catalyst was synthesised from sodium hydroxide, sodium silicate and alumina as chemical raw materials and was impregnated with rice husk silica by wet impregnation method, the catalyst were subsequently calcined at 550 0C for 6h the catalysts were characterised using XRD, FTIR and SEM. The formation of AlO4/SiO4 catalyst was confirmed by the analysis aforementioned. The XRD revealed that Zeolite X and Y synthesized has a faujasite phase with major peaks 230, 22.50 and 17.50, 180 in zeolite X and Y respectively, SEM confirmed the composition of crystallite shapes of irregular, cubic and rectangular shape. FTIR analyses revealed the presence of functional groups (The signal at the silica-alumina vibrational regions (1300 – 300 cm-1) indicates that SiO4 or AlO4 are linked) associated with Zeolites.